Conceptualizing of Academic Hardiness During Covid-19 pandemic of an Islamic Senior HighSchool in Malang, East Java - Akrim Akrim; Umiarso Umiarso (Yayasan Keluarga Guru Mandiri, 2022)
This research focuses on the process of establishing the Academic hardiness of the Aisyiyah Boarding School (ABM) high school students during the COVID-19 pandemic. As a form of one's firmness in facing academic challenges during the pandemic, Academic hardiness has an important position to be studied comprehensively and in-depth, especially in terms of students' academic resilience as study subjects. This research is based on Kobasa's Academic Hardiness Theory (AHT) and uses a qualitative approach to obtain descriptive data, observable behavior, and verbal data. Data collection methods used non-participant observation techniques, virtual interviews, and documentation studies. The data collected was then analyzed using the interactive model of Miles, Huberman, and Saldana. The conclusion of this research states that the academic hardiness of ABM students is formed through habituation activities in Islamic education. Empirically, the three cognitive evaluation processes (commitment, control, and challenge) are related to students' persistence when dealing with difficult e-learning designs. The implication of the results of the analysis of the process of forming the academic hardiness of students at ABM is the birth of new creations in improving the quality of Islamic education learning through optimizing the cognitive evaluation process of students.